The Rise and Fall of the HyFlex Approach in Mexico - Padilla Rodríguez, Brenda Cecilia (Association for Educational Communications & Technology, 2022)
During the Covid-19 pandemic, the world turned to online tools as a means of ensuring continued access to education, highlighting possibilities for innovation, particularly in contexts like Mexico, where the use of edtech was not previously prevalent. When educational institutions reopened their physical campuses, many schools and universities considered a hybrid, fexible (HyFlex) approach as a way of catering for diferent needs. While research fndings on students’ perspectives tend to be positive, the implementation of HyFlex courses has shown some challenges. Issues reported by teachers relate to poor technical infrastructure, work overload and lack of guidance. The initial excitement for the HyFlex approach has subdued. However, an openness to innovation is still there, ready to be exploited.